Analisis Faktor Penyebab Kecelakaan Lalu Lintas Pada Ruas Jalan Gubuk Klakah (Studi Kasus: Jalan Gubuk Klakah-Objek Wisata Bromo, Kabupaten Malang) - Rinse , Marta Yunita; Pandulu , Galih Damar; Arifianto , Andy Kristafi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Traffic accidents Traffic accidents are very common and cause a lot of losses. As a result of traffic accidents in the form of damage to public facilities and fatalities. victims who died. The objectives of the research are to determine the factors that trigger accidents, to determine influence of driver behavior on accident rates, to find efforts to minimize the risk of accidents. minimize the risk of accidents. Therefore, the collection of secondary data and primary data in this study with interview techniques by distributing questionnaires and documentation tools. by distributing questionnaires and documentation tools. In this study, researchers used sampling and population methods using slovin formula. The population that the researcher will take is the people of Gubuk Village, Klakah. Klakah. Based on the results of data analysis, it can be concluded that factors that cause traffic accidents on the Gubuk Highway section Klakah-Objek Bromo Tourism is a human factor of 26.40%, the factor of road / natural conditions of 11.88%, and the factor of road / natural conditions of 11.88%. road / natural conditions by 11.88% and vehicle factors by 15.97%, the influence of vehicle driver behavior on the number of accidents and the number of accidents. influence of vehicle driver behavior on the number of accidents and The influence of vehicle driver behavior on the number of accidents and the involvement of accidents on the Gubuk Klakah-Objek Wisata Road Section. Bromo is on the human factor of 26.40% which is aged 36>45 by 29,2%. Alternative solutions that need to be done are additional improvements such as road improvements (road shoulders) and the addition of road facilities such as the addition of warning signs. addition of warning signs, so that road users can understand and not violate applicable regulations. and also not violate applicable regulations.